Teacher Training in the Context of Rural Socioterritorial Diversity - Sônia Fátima Schwendler; Aline Nunes dos Santos (Universidade Federal do Rio Grande do Sul, 2022)
Educação do Campo (Education of the Countryside) has provided some spaces for the recognition of epistemic diversity and for decoloniality in teacher training for rural schools. The analysis is based on the development of an original curricular proposal - the Licentiate in Educação do Campo(LECAMPO), from the Federal University of Paraná, Seaside Sector, which is organized in different territories/classes to enable the access of settled, quilombola, indigenous, riverine, and family farmer communities to higher education. The empirical research involved observations and interviews with teachers and students using the methodology of oral story/life story in four LECAMPO classes, in the municipalities of Lapa, Cerro Azul, Adrianópolis, and Matinhos. The study infers that the introduction of the University in the context of rural socioterritorial diversity, through the pedagogy of alternation and itinerancy, has provided new meaning to the logic and epistemology of teacher training.